English language teaching and its impact our economy - Dilafruz Jurayeva Mirzamaxmudovna (Zien Journals, 2022)
This article highlights the importance attached to foreign languages in the Republic of Uzbekistan and the innovative technologies needed to study them.
Keywords: Foreign language; game; innovative technology; technological tools